Woodward procedure with intraoperative neuromonitoring for Sprengel deformity: a retrospective study with a mean 5-year follow-up - Zhang, Li; Cai, Haoqi; Huang, Yangbo; Yang, Mengting; Huang, Shi; Miao, Mingyuan; Cai, Haiqing; Wang, Zhigang (Frontiers in Pediatrics, 2025)
BackgroundThe Woodward procedure was designed to correct Sprengel deformity (SD) while brachial plexus injury remains a critical complication. This study aimed to assess the effectiveness of the Woodward procedure with clavicle osteotomy and intraoperative neuromonitoring (IONM) in enhancing postoperative functional outcomes, cosmetic appearance, and nerve injury prevention.MethodsWe retrospectively reviewed the records of patients who underwent the Woodward procedure with clavicle osteotomy and IONM for Sprengel deformity at our institution between January 2013 and May 2023. Patient demographics, clinical and cosmetic outcomes before and after surgery, and complications were analyzed.ResultsA total of 36 patients (female: male = 16:20) with a mean age of 4.1 ± 1.5 years were included, with a mean follow-up of 5.6 years. Intraoperatively, no IONM alerts occurred. At the latest follow-up, shoulder abduction improved by an average of 74°, and Cavendish grade improved from grade 3 or 4 preoperatively to grade 1 or 2. Radiographic analysis showed Rigault grade improvement from grade 3 to grade 1 or 2. Aside from a single instance of delayed wound healing and one case of hypertrophic scarring, no brachial plexus injuries or long-term complications were observed.ConclusionsWoodward procedure combined with clavicle osteotomy and IONM for SD patients is associated with significant improvement in postoperative functional outcome, cosmetic appearance, low risk of complications and high levels of satisfaction.